2023
DOI: 10.3389/fvets.2023.1090222
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus in white-nosed coatis (Nasua narica) in Mexico: what do we know so far?

Paola Puebla-Rodríguez,
Cenia Almazán-Marín,
Fabiola Garcés-Ayala
et al.

Abstract: Rabies is a neglected disease that affects all mammals. To determine the appropriate sanitary measures, the schedule of preventive medicine campaigns requires the proper identification of the variants of the virus circulating in the outbreaks, the species involved, and the interspecific and intraspecific virus movements. Urban rabies has been eradicated in developed countries and is being eradicated in some developing countries. In Europe and North America, oral vaccination programs for wildlife have been succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It is now sustained and transmitted by some species of wild mammals, most likely skunks. Its canine origin poses a serious risk of reintroducing the virus into canine populations if vaccination coverage is not maintained [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…It is now sustained and transmitted by some species of wild mammals, most likely skunks. Its canine origin poses a serious risk of reintroducing the virus into canine populations if vaccination coverage is not maintained [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic attributes of vectors, hosts, and pathogens, which determine the success of spread, replication, and transmission in animal and human populations [ 73 , 89 ], are also among the factors that act simultaneously and influence the dynamics of pathogen propagation [ 10 ]. We found that T .…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that by 2050, 2/3 of the world population will live in urban areas [ 109 ], which makes it necessary to protect urban residents from animal-transmitted diseases. In the YP, the dengue is one of the most emerging diseases ( Fig 4 ), but the circulation of other arboviruses-borne diseases, such as Zika, chikungunya, malaria, and West Nile virus, has also been confirmed, as well as viruses associated with bats, rodents, and other mammals [ 70 , 73 , 110 112 ].…”
Section: Discussionmentioning
confidence: 99%